The Dynamics of H2O Suspended by Multiple Shaped Cu Nanoadditives in Rotating System. (30th November 2021) - Adnan,; Khan, Umar; Ahmed, Naveed; Mohyud-Din, Syed Tauseef; Hamadneh, Nawaf N.; Khan, Ilyas; Andualem, Mulugeta
Abstract : Heat transfer investigation in the nanofluids is significant for real world applications. The investigation of heat transfer over a stretchable magnetized surface has broad applications in various industries. Therefore, heat transfer featuring in the nanofluid synthesized by various shaped Cu and H2 O is organized over a shrinking surface. The problem is organized properly via similarity equations by inducing the influences of magnetic field. Then, OVIM is adopted and performed the solutions for the particular model. The results are furnished for the governing quantities over the feasible region and deeply discussed in the view of their physical significance. It is examined that the nanoliquids angular motion and shear stresses drops by strengthen magnetic field effects. Moreover, nanoliquid containing brick Cu-particles is better heat conductor and could be used broadly for industrial applications as for as heat transport concerned. In end, authentication of the study is provided by comparing the results with previous science literature and an excellent agreement is seems between them.